MEDIATION ANALYSIS OF CUSTOMER SATISFACTION IN THE RELATIONSHIP BETWEEN EXPERIENTIAL MARKETING AND CUSTOMER LOYALTY OF THE GOJEK APPLICATION IN SEMARANG - Muflihah, Robingatul; Zusrony, Edwin; Kusumo, Haryo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study has been structured to investigate how experiential marketing influences customer retention through customer satisfaction. It is a quantitative study with a population consisting of Gojek users in the Semarang City. The sampling technique is non-random sampling with a purposive sampling technique. The number of respondents is limited to 50 Gojek users in theMillennial and Generation Z categories. The research instrument is a structured questionnaire and the obtained responses will be measured using a Likert scale. For this research, the data analysis technique selected is Partial Least Square PLS) and the required calculations will be done using SmartPLS 4.0 software. The result of this study shows that there is a positive and significant effect of experiential marketing on customer satisfaction and customer loyalty, also customer satisfaction positively affects customer loyalty, and customer satisfaction can be considered as a mediator in the effect of experiential marketing on customer loyalty. These results support the significance of positive customer experiences as a core marketing tool to reinforce loyalty.